Crianças negras em imagens do século XIX - Jovino, Ione da Silva (2010)
This research was based on the need of understanding the presence of black children in the 19th century and as a consequence understand childhood from this perspective. It intended to show how black children could be seen through images produced in the 19th century, which were selected from a corpus of engravings by Jean-Baptiste Debret and portraits by Militão Augusto de Azevedo. To discuss how the black children were represented in the images we tried to establish a relation between the history of children and childhood in Brazil, as well as to point out the importance of the image to the comprehension of the historical construction of the Brazilian black childhood framework. The analysis was based on a Foucaultian perspective, in which we aimed at focusing not on what the images hid, but at what these images showed as possibilities for these children and for black childhood as a whole in the 19th century. In addition, we analyzed the literature concerning slavery to understand childhood slavery presented in the famous works of Debret. We also searched other images that revealed different aspects of black childhood. This effort allowed the selection of portraits made by Militão, a gallery of unknown people, which showed black children quite differently from the first images, they were part of families or communities that used photography to keep their memories and of their groups so that they could perpetuate the images of these children. The analysis allowed the visualization of a feeling of black childhood, demonstrated by the signs of how children were taken care of which were preserved and recreated by black adults in the Brazilian slavery context.